1998
DOI: 10.1001/jama.279.18.1474
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Child's Sex on Medulloblastoma Outcome

Abstract: Context.-Aggressive treatment of medulloblastoma, the most common pediatric brain tumor, has not improved survival. Identifying better prognostic indicators may warrant less morbid therapy.Objective.-To investigate the role of sex on outcome of medulloblastoma. Design.-Retrospective study of significant factors for survival with a median follow-up of 82 months. Setting.-University medical center. Patients.-A total of 109 consecutive, pediatric patients treated for primary medulloblastoma from 1970 to 1995 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
2
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 24 publications
4
38
2
3
Order By: Relevance
“…Male patients presented significantly reduced survival as compared to females (p=0.002). This finding was also reported by Jaros et al and weil et al 14,18 . As previously described by other authors 2,15 , the variables age, histological subtype, and presence of residual tumor did not have a statistically significant correlation with survival.…”
Section: Mb Is a Cerebellar Embryonal Tumor Of Grade IV (Who)supporting
confidence: 90%
“…Male patients presented significantly reduced survival as compared to females (p=0.002). This finding was also reported by Jaros et al and weil et al 14,18 . As previously described by other authors 2,15 , the variables age, histological subtype, and presence of residual tumor did not have a statistically significant correlation with survival.…”
Section: Mb Is a Cerebellar Embryonal Tumor Of Grade IV (Who)supporting
confidence: 90%
“…This has been seen for medulloblastomas in other studies as well. 48,49 In 1 study, the effect was seen only for girls .3 years old. 49 In our data set, the effect was seen for girls $1 year (data not shown).…”
Section: -2004mentioning
confidence: 86%
“…23 Some explanations for these findings have been suggested as follows: a behavior of medulloblastoma intrinsically different between sexes, favoring a more indolent, well-localized, and more easily resectable form in female patients; the presence of female hormones, which may provide protection against tumor recurrence; and the precocious puberty induced by therapy that confers a survival advantage in children as well as the fact that girls were usually more sensitive to therapy. 32,45,47 However, we have not been able to determine particular features of the tumors in our female patients that might have suggested such different behavior. This sex-based difference for survival and disease control remains an enigma and should be viewed cautiously because of the small sample size of our series.…”
Section: Prognostic Factorsmentioning
confidence: 88%
“…This impact has already been reported in other adult series 12,18,32,40 as well as in children. 13,45,47 Others 1,3,4,10,25,26,36 have found that sex did not affect survival or, on the contrary, noted better outcome for male patients. 23 Some explanations for these findings have been suggested as follows: a behavior of medulloblastoma intrinsically different between sexes, favoring a more indolent, well-localized, and more easily resectable form in female patients; the presence of female hormones, which may provide protection against tumor recurrence; and the precocious puberty induced by therapy that confers a survival advantage in children as well as the fact that girls were usually more sensitive to therapy.…”
Section: Prognostic Factorsmentioning
confidence: 99%